The Role of Cadres to Educate on the Activities of the Youth Integrated Service Post in Jamika Village Bojongloa Kaler Bandung - Rara Pringgandinie, Desty; Abdul Muluk, Kiki; Lafia, Rizqi (Jurnal Edusci, 2024)
Adolescence is a transitional phase from childhood to adulthood. This phase has many physical and psychological changes that can cause various problems. The RW 09 Jamika integrated youth service post is a form of community-based health effort (UKBM) to bring adolescent health services closer to the RW 09 area. It has a function as a means of nonformal education regarding adolescent health. Implementing the integrated youth service post in RW 09 Jamika is suspected to have been more optimal for educating adolescents. This is because the youth of RW 09 Jamika have problems including (1) having anemia, (2) smoking habit, (3) the habit of staying up late, and (4) rarely doing physical activity. The aims of this study were (1) to describe the role of cadres in educating youth at RW 09 Jamika integrated service post activities; (2) to describe the inhibiting factors for cadres to help educate youth in youth integrated service post activities in RW 09 Jamika; and (3) provide solutions in increasing the role of cadres in educating youth integrated service post activities in RW 09 Jamika. The research method used is qualitative. This research data collection technique consists of interviews, documentation, and observation. The results of this study are (1) the role of the cadres is carrying out peer counseling, implementing the five-desk principle, and providing multiple questionnaires; (2) the inhibiting factors for the role of cadres in educating are the knowledge of cadres who have not mastered it optimally, limited time for training cadres and youth to be carried out by health center staff, and limited infrastructure; and (3) the solution to increasing the role of cadres in educating is to conduct coaching for cadres, scheduling according to the schedule of puskesmas officers or youth activities, and collaborating with related devices to help fulfill facilities and infrastructure.